Students' Learning Disability of Elementary School in Tangerang : Identification Students Learning Disabilities, Factors and Teacher's Effort - Asep Supena; Lesti Kaslati Siregar (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2020)
This study aims to investigate student's learning disability, factors of learning disability and teacher efforts to deal with students who have learning difficulties in elementary school Tangerang Region, Indonesia, and the implications of this study is to get the data regarding student's disability in learning, the factor that caused it, and teacher's efforts in dealing with students who have learning difficulties. This study employed a descriptive qualitative research method. Data collection techniques by an in-depth interview. Interview guides in the form of a group of in-depth questions about learning disabilities. Results showed that there are 19 students who had learning disabilities. Students with learning disabilities in elementary schools found for slow learners, children with special need, and student with malnutrition. the factor that caused students learning disabilities were parents’ gadget influence the lack of parental attention lack of parental knowledge. Furthermore, the efforts made by the teacher so far have been giving more attention to students such as giving extra hours at school, positioning the child to sit in the front position, communicating intensely to the child's development to parents.